2022
DOI: 10.15252/embr.202153955
|View full text |Cite
|
Sign up to set email alerts
|

Cardio‐respiratory and phenotypic rescue of dystrophin/utrophin‐deficient mice by combination therapy

Abstract: Duchenne muscular dystrophy (DMD) is a systemic progressive muscular disease caused by frame‐disrupting mutations in the DMD gene. Although exon‐skipping antisense oligonucleotides (AOs) are clinically approved and can correct DMD, insufficient muscle delivery limits efficacy. If AO activity can be enhanced by safe dietary supplements, clinical trials for efficacy can be undertaken rapidly to benefit patients. We showed previously that intravenous glycine enhanced phosphorodiamidate morpholino oligomer (PMO) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Wild‐type (WT) mice were purchased from Beijing Vital River Laboratory Animal Technology Company. DP1 global knockout (DP1 KO), DP2 KO, DP2 flox/flox (DP2 fl/fl ) and MDX mice were maintained in our laboratory 16,17 . DP2 fl/fl mice were crossed with human skeletal actin Cre (HSA Cre ) mice 18 to generate DP2 fl/fl HSA Cre mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Wild‐type (WT) mice were purchased from Beijing Vital River Laboratory Animal Technology Company. DP1 global knockout (DP1 KO), DP2 KO, DP2 flox/flox (DP2 fl/fl ) and MDX mice were maintained in our laboratory 16,17 . DP2 fl/fl mice were crossed with human skeletal actin Cre (HSA Cre ) mice 18 to generate DP2 fl/fl HSA Cre mice.…”
Section: Methodsmentioning
confidence: 99%
“…DP1 global knockout (DP1 KO), DP2 KO, DP2 flox/flox (DP2 fl/fl ) and MDX mice were maintained in our laboratory. 16 , 17 DP2 fl/fl mice were crossed with human skeletal actin Cre (HSA Cre ) mice 18 to generate DP2 fl/fl HSA Cre mice. Mice were maintained in an environment with a controlled temperature (22 ± 1°C) and relative humidity (50 ± 5%) on a 12:12‐h light/dark cycle, with free access to a normal chow diet (ND) and water.…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous studies that demonstrated an improvement of phosphorodiamidate morpholino oligomer (PMO) delivery to peripheral muscle in mdx mice by intravenous administration of glycine, the group conducted by Lin analyzed the effect of oral glycine and metformin alongside PMO in dystrophin/utrophin double knock-out (DKO) mice [55]. Thus, without any toxicity that could be detected and with a life span extension, the scientists demonstrated improvements in the cardio-respiratory and skeletal systems and a phenotypic rescue in DKO mice [55].…”
Section: Metformin: a Pleiotropic Drugmentioning
confidence: 99%